Surgical outcomes of patients with early cervical cancer treated with radical hysterectomy in a tertiary care hospital - R., Rameshkumar; Kulkarni, Namrata; Sharma, Anuriti; Kulkarni, Chaitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This study was undertaken to evaluate the surgical outcomes of patients with early cervical cancer treated with radical hysterectomy. Methods: A total of 50 patients who underwent modified radical hysterectomy between April 2006 and April 2016 at Shri Dharmasthala Manjunatheswara medical college and hospital, Dharwad, Karnataka were retrospectively reviewed. The analysis included clinical and pathologic variables including age, tumour size, clinical stage, lymphovascular space involvement, tumour type and grade, lymph node metastases, surgical margin involvement, intraoperative and postoperative complications and pattern of adjuvant therapy were analysed. Results: The median age of the patient who underwent radical hysterectomy was 47.8 years, the mean parity being 3.6. Histologically, the most common type of malignancy encountered was squamous cell carcinoma of the cervix, which occurred in 42 patients (84 %). 8 (16%) showed involvement of 1 or more lymph nodes and evidence of lymphovascular invasion. Involvement of the resected vaginal margins was noted in 11 patients (22%). The average hospital stay was 19.8 days, the prolonged stay resulting from postoperative morbidity. Postoperative concurrent chemoradiation with cisplatin was administered in eight (16%) cases due to pelvic lymph node metastases. Postoperative vaginal brachytherapy was given in 11 (22%) cases because of positive vaginal margins. Conclusions: The present study shows that general gynaecologists with signiﬁcant experience in general gynaecologic surgery may, with adequate but abbreviated training, become competent in performing a modiﬁed radical hysterectomy.